2017
DOI: 10.1186/s12864-017-3752-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study confirm major QTL for backfat fatty acid composition on SSC14 in Duroc pigs

Abstract: BackgroundFatty acid composition contributes importantly to meat quality and is essential to the nutritional value of the meat. Identification of genetic factors underlying levels of fatty acids can be used to breed for pigs with healthier meat. The aim of this study was to conduct genome-wide association studies (GWAS) to identify QTL regions affecting fatty acid composition in backfat from the pig breeds Duroc and Landrace.ResultsUsing data from the Axiom porcine 660 K array, we performed GWAS on 454 Duroc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 56 publications
(84 reference statements)
4
29
1
Order By: Relevance
“…It has been widely reported that the fatty acid composition of meat can be affected by various factors such as age, sex, and rearing conditions of the animals [7][8][9][10]. In addition, fatty acid compositions are heritable traits, with heritability ranging between 0.2 and 0.6 in various populations of pigs [11,12]. Chickens and ducks of different breeds have been shown to vary in fatty acid composition, suggesting that genetic factors may influence fatty acid composition, and breeding poultry for favorable fatty acid composition is possible [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that the fatty acid composition of meat can be affected by various factors such as age, sex, and rearing conditions of the animals [7][8][9][10]. In addition, fatty acid compositions are heritable traits, with heritability ranging between 0.2 and 0.6 in various populations of pigs [11,12]. Chickens and ducks of different breeds have been shown to vary in fatty acid composition, suggesting that genetic factors may influence fatty acid composition, and breeding poultry for favorable fatty acid composition is possible [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, Wood et al (1989) reported that the contents of C18:2n-6 provides the best prediction of fat firmness. According to Seman (2008), the melting point of C18:2n-6 is -5°C which is considerably lower than that of C18:0 (70.1°C) and even C18:1(16.3°C). The low melting point of the fat is associated is various quality issues in the meat products such as reduced cohesiveness (Gandemer et al 2002) and separation between the fat and muscle in dry cured products, as well as softer, undesirable texture and fat smearing in fresh sausages (Legan et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Adipose tissue is of major importance in the farm animals, since its percentage of the body weight is a major determinant for the efficiency of transferring nutrients from feed into food products and thus for the economic value of meat producing animals (Sauerwein et al 2014). In addition to its functions as an energy reservoir and endocrine organ, the adipose tissue of pigs, is an important component of meat together with the other major componentsprotein, water, and ash (Seman 2008). Much of the carcass fat accumulates in the subcutaneous depots (backfat) surrounding the major wholesale cuts, and other fat exists as intermuscular, lying between the muscles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While PUFA are mainly related to nutrition as they cannot be synthesised de novo in pigs and come from exogenous supplies [31], their relative quantities in pig tissues can be altered by oxidation processes and other fatty acids synthesised de novo. In the context of the variability between studies in terms of nutrition and final body weight and age, it is difficult to evaluate to which degree the collected data and the differences observed were influenced by genetic or production system factors, but the importance of the genetic control of fatty acid composition and potential for selective breeding has been emphasised in different pig genotypes [32][33][34][35]. Regarding the nutritional value of pork which has generally high n-6/n-3 ratio, much above the recommended one (<5), studies on local pig breeds show huge variability; however, in some breeds, in particular, Iberian in 'montanera' production, the observed values approach the mentioned recommendation [15,36,37].…”
Section: Meat and Fat Qualitymentioning
confidence: 99%